Attitudes of U.S. Wind Turbine Neighbors: Analysis of a Nationwide Survey. (November 2019) - Hoen, Ben; Firestone, Jeremy; Rand, Joseph; Elliot, Debi; Hübner, Gundula; Pohl, Johannes; Wiser, Ryan; Lantz, Eric; Haac, T. Ryan; Kaliski, Ken
Abstract: Experts predict continuing deployment of wind turbines in the United States, which will create more interactions between turbines and surrounding communities. Policymakers can benefit from analyses of existing wind projects that enable them to better understand likely effects on residents around proposed projects. Our analysis of a randomly drawn, representative national survey of 1705 existing U.S. wind project neighbors provides previously unavailable detail about factors influencing the attitudes of these neighbors toward their local wind projects. Overall, we find positive-leaning attitudes, which improve over time as individuals self-select into communities near existing wind projects. Hearing wind turbines leads to less-positive attitudes, although living very near to turbines does not, nor does seeing wind turbines. In fact, our findings suggest complex relationships among nearby residents' attitudes, their perceptions about the particular fit of turbines within their landscape and community, and their perceptions of wind project impacts on property values. These findings—along with the positive correlation between perceived planning-process fairness and attitude—suggest areas of focus for wind project development that may influence social outcomes and acceptance of wind energy. The concluding discussion provides a number of policy and future research recommendations based on the research. Highlights: A nationally-representative random sample of 1705 U.S. wind project neighbors. Positive attitudes toward the local turbines outweighed negative by a 7:1 ratio. The largest cohort, those living within 0.8 km of a turbine, had a similar ratio. Attitudes improve over time as more-positive residents move into the area. Perceived planning fairness and turbines' landscape fit help explain attitude differences.